FORMULATION AND ACTIVITY TESTING OF AN ANTI-ACNE MICELLAR WATER FORMULATION CONTAINING BINAHONG LEAF EXTRACT (ANREDERA CORDIFOLIA TEN) AGAINST PROPIONIBACTERIUM ACNES - Sintia Nurmala; Kartika Sari (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Acne (Acne vulgaris) is a chronic inflammation of the pilosebaceous glands caused by the bacteria Propionibacterium acnes and is a common skin problem, especially in adolescents with a prevalence of up to 85%. Binahong leaves (Anredera cordifolia) are known to contain secondary metabolites such as flavonoids, saponins, tannins, and alkaloids that have antibacterial potential. This study aims to formulate micellar water preparations from binahong leaf ethanol extract as an anti-acne facial cleanser and to evaluate its physical, chemical characteristics and antibacterial activity against Propionibacterium acnes bacteria. This study used a laboratory experimental method. Binahong leaf extract was obtained through a maceration method using 70% ethanol with a yield of 16.4%. Micellar water preparations were formulated in three variations of extract concentrations, namely 1%, 3% and 5%. Evaluation of the preparations included organoleptic tests, homogeneity, pH, viscosity, cleaning power, stability using the cycling test method and antibacterial activity testing using the disc diffusion method with clindamycin as a positive control. The results of the study showed that binahong leaf extract positively contained flavonoids, saponins, tannins, and alkaloids. All micellar water preparation formulas had good physical and chemical characteristics, were homogeneous, stable during testing, and had a pH that matched the physiological pH of facial skin. The results of the antibacterial activity test showed that preparations F1, F2 and F3 had antibacterial activity in the strong category with an average inhibition zone diameter of 11.35 ± 1.11 mm; 11.97 ± 2.40 mm; and 12.92 ± 0.56 mm. Based on the results of the study, the formula with a 5% extract concentration showed the best antibacterial activity against Propionibacterium acnes.